2002
DOI: 10.1001/archpsyc.59.11.1027
|View full text |Cite
|
Sign up to set email alerts
|

Increased Amygdala Activation to Angry and Contemptuous Faces in Generalized Social Phobia

Abstract: These findings are consistent with a role for differential amygdala (and associated limbic) functioning in GSP. The pronounced response to contemptuous and angry facial expressions suggests that the amygdala in GSP may be particularly active in the processing of disorder-salient stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
378
8
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 530 publications
(427 citation statements)
references
References 62 publications
33
378
8
8
Order By: Relevance
“…Otherwise, other gaze could -of fearful expressions, or could be even reassuring, as in the case of averted gaze combined with happy and neutral expressions. The present data strictly fit evidence on social phobia (Horley et al 2004;Moukheiber et al 2010;Stein et al 2002) and are consistent with the self-relevance may represent a powerful signal of danger for introverts individuals, they would (likely implicitly) try to avoid interaction with eye gaze in the attempt to reduce threatrelated overarousal, but only when gaze is combined with angry expressions. On the contrary, introverts are encouraged in eye contact expressions.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Otherwise, other gaze could -of fearful expressions, or could be even reassuring, as in the case of averted gaze combined with happy and neutral expressions. The present data strictly fit evidence on social phobia (Horley et al 2004;Moukheiber et al 2010;Stein et al 2002) and are consistent with the self-relevance may represent a powerful signal of danger for introverts individuals, they would (likely implicitly) try to avoid interaction with eye gaze in the attempt to reduce threatrelated overarousal, but only when gaze is combined with angry expressions. On the contrary, introverts are encouraged in eye contact expressions.…”
supporting
confidence: 88%
“…Provided that introversion is related to high levels of arousal to social signals (Eysenck 1967), and consistent with evidence on social phobia (Horley et al 2004;Moukheiber et al 2010;Stein et al 2002), we expected that introverts would not show the gaze congruency effect in presence of threatening, and in particular angry, facial stimuli relative to non-threatening (happy and neutral) expressions. Importantly, since previous research showed that the gaze-cueing effect with emotional expressions can interact with trait anxiety (Frischen et al 2007;Fox et al 2007;Mathews et al 2003), in the present experiment we also assessed self-reported levels of trait anxiety to explore the possible relationships between anxiety and intro-/extraversion in modulation of the gaze-cueing effect.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The presented data also supports the view that enhanced, rather than weak amygdala function may be part of the pathology in autism. In accordance with these hypotheses are the findings that a hyperreactive amygdala has been associated with social phobia (Stein et al, 2002;Tillfors, 2004), whereas enhanced sociability as encountered in Williams syndrome, is associated with a hyporesponsive amygdala (Meyer-Lindenberg et al, 2005). A recent study screening for autism-like symptoms in children with mood and anxiety disorders also found that up to 62% of these children fall into the autistic spectrum and might qualify for a possible diagnosis of autism (Towbin et al, 2005).…”
Section: Indirect Effects Of Non-amygdala Regionsmentioning
confidence: 76%
“…Psychopaths, however, also show lack of fear (Herpertz et al, 2001). In contrast, individuals suffering from social phobia show increased amygdala activation (Stein, Goldin, Sareen, Zorilla, & Brown, 2002). Because amygdala deficits may be developmental in psychopaths, their lack of experience in fear recognition may reduce their ability to appraise cues for fear (see Blair this issue).…”
Section: Limitations To a Strict Ofc Account Of Psychopathymentioning
confidence: 99%